Frozen overnight: Acute orbital apex syndrome caused by aspergillosis. Issue 3 (May 2023) - Pellegrini, Francesco; Mandarà, Erika; Stafa, Altin; Meli, Salvatore
Purpose: to describe a rare case of orbital apex syndrome caused by aspergillosis with acute presentation. Case description: retrospective case report of a 70-year-old man who developed unilateral ophthalmoplegia overnight. He was initially given the diagnosis of suspect Tolosa-Hunt syndrome, but biopsy of the involved tissue showed aspergillosis. Conclusion: orbital apex syndrome caused by fungal disease is a life-threatening condition that should be promptly diagnosed and treated. It may present acutely and should not be misdiagnosed as Tolosa-Hunt syndrome. To our knowledge this is the first such case report in the English ophthalmic language Literature.